Active Learning Strategies in the Environmental Engineering Course: A Case Study at Curtin University Malaysia (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
The current teaching approach of the undergraduate subject is very dependent on conventional methods, in which less participation and contribution of the students during the learning process. Active learning refers to any approach to instruction in which all students are required to involve in the learning process. The objective of the manuscript is to evaluate the application of active learning in teaching the compulsory course in environmental engineering department curriculum, Curtin University Malaysia. Green engineering is a mandatory unit in 3rd year of Department of Environmental Engineering. That is an approach of the design, process, product, and commercialization that follow environmentally conscious attitude, principles and values combined with multi-disciplinary engineering science in order to minimize pollutant and promote local and global sustainability. Experts have developed a simple approach that connecting the classical lecture-presentation and active engagement of the students with the course materials through Problem-Based Learning, Interactive Class Learning, and Project-Based Learning. Introducing the active learning to the students on solving problems have improved the students’ ability in achieving the course objectives and also the program objectives of the Department of Environmental Engineering, Curtin University Malaysia. The attainment of each assessment by the students and student evaluations indicated that the students’ achievement and retention of information have greatly improved. This improvement includes high student attendance and participation, high grades, and great student satisfaction.